Discriminant Analysis; Telecommunications and Economic Development; Taking a Stand: Extension and Public Policy Issues - Jim Shaner; Mason E. Miller (Journal of Applied Communications, 1984)
Reviews of "Discriminant Analysis," by William R. Klecka; Telecommunications and Economic Development by Robert J. Saunders, Jeremy J. Warford, and Bjorn Wellenius; "Taking a Stand: Extension and Public Policy Issues," by Richard L. Barrows.